Purification and Characterization of Nitphym, a Robust Thermostable Nitrilase From Paraburkholderia phymatum - Bessonnet, Thomas; Mariage, Aline; Petit, Jean-Louis; Pellouin, Virginie; Debard, Adrien; Zaparucha, Anne; Vergne-Vaxelaire, Carine; de Berardinis, Véronique (Frontiers in Bioengineering and Biotechnology, 2021)
Despite the success of some nitrilases in industrial applications, there is a constant demand to broaden the catalog of these hydrolases, especially robust ones with high operational stability. By using the criteria of thermoresistance to screen a collection of candidate enzymes heterologously expressed in Escherichia coli, the enzyme Nitphym from the mesophilic organism Paraburkholderia phymatum was selected and further characterized. Its quick and efficient purification by heat treatment is of major interest for large scale applications. The purified nitrilase displayed a high thermostability with 90% of remaining activity after 2 days at 30°C and a half-life of 18 h at 60°C, together with a broad pH range of 5.5-8.5. Its high resistance to various miscible co-solvents and tolerance to high substrate loadings enabled the quantitative conversion of 65.5 g L-1 of 3-phenylpropionitrile into 3-phenylpropionic acid at 50°C in 8 h at low enzyme loadings of 0.5 g L-1, with an isolated yield of 90%. This study highlights that thermophilic organisms are not the only source of industrially-relevant thermostable enzymes and extends the scope of efficient nitrilases for the hydrolysis of a wide range of nitriles, especially trans-cinnamonitrile, terephtalonitrile, cyanopyridines and 3-phenylpropionitrile.